Professor Stefan ERNST - CHORAZEWSKI, Mirosław (Archives of Acoustics, 2014)
It is with great sadness that we inform our readers about the recent death of Professor Stefan Ernst. Stefan Ernst was born in Piaśniki, Upper Silesia, on November 03, 1934, to parents of Polish-German descent. His primary education started during the war at a German-speaking school in Wirek and continued in Olesno, where he also got his secondary education. As chemistry studies were not yet available at the University of Wrocław in 1953, he started studying biology and switched to chemistry a year later. He received his master’s degree in chemistry in 1959, as one of the first graduates in that major. Then, he started his work on application of thermodynamics and molecular acoustics in investigation of liquid phases under the guidance of the Prof. Bogusława Jeżowska-Trzebiatowska. On 28 November 1967, he defended his PhD thesis entitled “Association-Dissociation Equilibria and the Structure of Uranyl Compounds in Organic Solvents” at the University of Wrocław. Professor Stefan Ernst was a linguist, a polyglot, a renowned thermodynamisist and a researcher of molecular acoustics. With great regret and shock we have learned of his sudden and unexpected death on August 03, 2014, in a hospital in Kraków.